AN APPROACH TO INVESTMENT DECISION TOWARDS AN ISLAMIC ANALYSIS - Muqorobin, Masyhudi (Jurnal Ekonomi & Studi Pembangunan, 2004)
The controversy among Islamic economists concerning investment decision criteria Jhr the project evaluation principally centers around the issue of discounting factor. This closely associates with the interest that Islam prohibits. Various papers have been published, either due to publication in journals or seminars and symposia, providing sophisticated analysis for seeking any solution to the problem. Unfortunately, this issue has remained unsettled, rather seemingly become more complicated.This paper attempts to analyze the issue from the fundamental ideas of criteria determination. Generally speaking, a project is undertaken after the evaluation of its Feasibility. Neoclassical economics has developed the standard of valuation from the point of view of profitability. This lies on the concept of inter-temporal choices and therefore time preference consumption on the one hand, with Fisherian approach that makes the indifference curves interplay with its constraint, production possibility, and individual’s income. This process is simultaneously determined by the rate of interest. The problem is of dealing with this established concept by eliminating its fundamental instrument, interest rate. Keynesian analysis comes up in the discussion to consider an extension to such an approach in dealing with macro concept of investment decision criteria. However the road towards superiority of Islam is not supposed to be merely in its ethical precept, but also theoretically and empirically verified. This effort with its limitations provides the answer.